A high sensitivity refractive index sensor based on photonic crystal fibre Mach–Zehnder interferometer. Issue 16 (8th September 2017) - Wang, Qi; Zhao, Wanming; Wang, Botao; Hu, Haifeng; Li, Jin
Abstract: A compact and high sensitivity refractive index sensor based on a photonic crystal fibre Mach–Zehnder mode–mode interferometer is proposed. The sensing part is formed by in fibre SMF-PCF-SMF structure (SMF: single-mode fibre; PCF: photonic crystal fibre) using fusion splicing method. The fully collapse air holes of photonic crystal fibre make coupling of fibre core and cladding mode in the splicing collapse region which establish a Mach–Zehnder interferometer. The Mach–Zehnder interferometers with different photonic crystal fibre length are fabricated to investigate refractive index sensing characteristics. The refractive index measuring sensitivity can reach 224.2 nm/RIU (RIU: Refractive Index Unit) with a length of PCF L  = 4 cm, experimentally. The proposed refractive index sensor is attractive due to its simple production process, compact size and high sensitivity.